Pengaruh Quick Ratio (QR) dan Debt to Equity Ratio (DER) Terhadap Return On Asset (ROA) pada PT X Periode 2014 -2023 - Bella Dwi Yulianti; I Gede Marendra (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the effect of Quick Ratio (QR) and Debt to Equity Ratio (DER) on Return on Assets (ROA), both partially and simultaneously, at PT X during the period 2014–2023. The background of this study is based on the importance of liquidity and capital structure in influencing a company's ability to generate profits. QR is used as an indicator of company liquidity, while DER reflects the proportion of debt usage in the capital structure. ROA is chosen as a measure of profitability because it illustrates the company's effectiveness in utilizing total assets to generate profits. The research method used is a quantitative method. The study population consists of all annual financial reports of PT X, with samples in the form of financial position reports and income statements from 2014 to 2023. Data analysis was carried out through several stages, namely descriptive analysis, classical assumption tests, coefficient of determination tests, multiple linear regression, and hypothesis testing to examine the relationship between variables. The results of the study indicate that partially the Quick Ratio has no significant effect on Return on Assets, with a calculated t value of 1.409 smaller than the t table of 2.365 and a significance value of 0.199 which is greater than 0.05. This finding indicates that the company's liquidity level has not been able to directly increase profitability. Furthermore, the Debt to Equity Ratio is also proven to have no significant effect on Return on Assets. This is indicated by a calculated t value of -2.299 which is smaller than the t table of 2.365 and a significance value of 0.055, still above the 0.05 limit. Thus, the company's capital structure through DER does not have a significant partial contribution to ROA.